2019
DOI: 10.1634/theoncologist.2019-0600
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Analysis for the Assessment of Sarcopenia in Patients with Cancer: A Systematic Review

Abstract: Background. The loss of muscle mass, known as sarcopenia, is a natural process of aging that is associated with adverse health outcomes regardless of age. Because cancer is a disease of aging, interest in sarcopenia and its potential impact in multiple cancer populations has increased significantly. Bioelectrical impedance analysis (BIA) is a guideline-accepted method for sarcopenia detection. This systematic review assesses the literature pertaining to BIA use in the detection of sarcopenia in adults with can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 73 publications
(257 reference statements)
1
64
0
1
Order By: Relevance
“…On the other hand, MRI, CT and DXA are expensive and hard to reach; we preferred BIA, since it is more accessible and inexpensive compared to the other methods. 38 As a result, loss of muscle strength can be frequently observed among patients with RA. Apart from age, gender, and disease duration, high disease activity is the most important preventable factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, MRI, CT and DXA are expensive and hard to reach; we preferred BIA, since it is more accessible and inexpensive compared to the other methods. 38 As a result, loss of muscle strength can be frequently observed among patients with RA. Apart from age, gender, and disease duration, high disease activity is the most important preventable factor.…”
Section: Discussionmentioning
confidence: 99%
“…Also DXA is another recommended tool for assessment of muscle mass. On the other hand, MRI, CT and DXA are expensive and hard to reach; we preferred BIA, since it is more accessible and inexpensive compared to the other methods 38 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, muscle mass was measured through bioelectrical impedance analysis (BIA). This method was chosen as it utilizes an inexpensive device and portable equipment, and it has been accepted under the guidelines of the European Working Group on Sarcopenia in Older People (EWGSOP) and AWGS [ 10 , 12 , 13 ]. The muscle mass was calculated using the following BIA equation of Janssen et al [ 14 ] which is where Ht is height in centimeters; BIA resistance is resistance in ohms:…”
Section: Methodsmentioning
confidence: 99%
“…BIA is a simple and non-invasive tool that can be used to assess frailty, including sarcopenia (11,16), malnutrition, and cancer cachexia (17,18). A recent review (19) reported that BIA is an accurate method for detecting sarcopenia in adults with cancer prior to treatment and is a viable alternative to CT, dual-energy X-ray absorptiometry, and magnetic resonance imaging in oncology clinical practice. In the review, all articles defined sarcopenia using SMI or FFMI, as measured by BIA.…”
Section: Discussionmentioning
confidence: 99%